PENINGKATAN KUALITAS SDM KELOMPOK TANI DALAM PENGOLAHAN PAKAN TERNAK BERBAHAN BAKU ALAMI - Syamsir Syamsir; Jumiati Jumiati; Ideal Putra (Faculty of Social Science, Universitas Negeri Padang, 2020)
This paper was abstracted from writer experiences in conducting the second year Community Service program among farmer group organizations in Anduriang Village at Padang Pariaman Regency. This program was aimed at increasing the knowledge and skills of farmer groups’ human resources in processing animal feed made from natural raw materials, especially from the golden snail, which has often been the enemy of farmers all this time. This study was inspired by various conditions that indicated the powerless of the farmer groups in overcoming the problem of golden snail pests in the Anduriang Village at Padang Pariaman Regency. This issue was reflected in part from the lack of understanding and awareness of farmers in controlling the golden snail pests. Based on this condition, various farmer empowerment programs were needed to be implemented in the form of increasing the farmers’ knowledge and skills in economic development of the society, particularly for the farmer group as target groups of this program. These empowerment programs needed to be conducted collaboratively and synergistically between the local government and universities.